Farmers’ Perceptions and Experiences on Family Nutrition Fulfillment and Mental Health Management in Rural Indonesia - Ryadi, Yusuf; Dewi, Mira; Ichsan, Burhannudin; Aryoseto, Lukman; Hartini, Riati Sri (UNUSA Press, 2025)
Introduction: Farmers in rural Indonesia face challenges in maintaining nutritional adequacy and mental health due to economic instability, crop failure risks, and fluctuating commodity prices. Limited empirical evidence exists on how these factors intersect within farming communities. Objective: This study aims to explore farmers' perceptions and experiences regarding nutrition and mental health among farmer groups in three rural districts of Indonesia. Methods: A qualitative study was conducted with 36 farmers (aged 25–65 years; all males) from Kulonprogo, Boyolali, and Bogor, selected purposively. Data were collected through focus group discussions and analyzed using inductive qualitative content analysis based on Graneheim and Lundman’s framework and processed with enVivo® software. Results: The main stressors identified were economic hardship, crop failure, debt and unstable commodity prices. Food decision-making was largely determined by wives, with children’s needs prioritized. While severe food insecurity was not reported, mild to moderate food insecurity characterized by limited dietary diversity was common. Coping strategies included additional income-generating activities, utilizing homegrown produce, and borrowing from relatives or neighbors. Conclusions: Findings indicate a strong interrelation between food insecurity and mental distress among farmers. Interventions that integrate nutrition improvement and mental health support alongside economic and agricultural policy reforms are essential to enhance farmers’ well-being.